Revitalisasi Integrasi Nalar Bayani, ‘Irfani dan Burhani dalam Pengembangan Pendidikan Pesantren - Mohamad Aso Samsudin (Program Pascasarjana Universitas Ibrahimy, 2019)
Along with the development of science and technology, Islamic education is challenged to participate in colouring and adapting the global world. This challenge is addressed differently; there are two attitudes in response to the development of western science and technology. First, cynicism towards the progress of the west. Secondly, appreciative attitude towards western progress. Both are used as benchmarks for the development of education. Islamic boarding schools appreciate the progress of western science from the good side by accrediting it that does not conflict with Islamic values ​​and still maintains Islamic scientific traditions.